The nutritional content of bilih fish (Mystacoleucus padangensis blkr) eggs waste as source of fish feed material - Syandri, Hafrijal (Jurnal Akuakultur Indonesia, 2011)
The purpose of study was to know nutrient content of bilih fish Mystacoleucus padangenesis Blkr eggs meal to provide basic information for local material based fish feed development. The eggs were collected from fishermen. Parameters observed were proximate (protein, fat, moisture and ash), minerals (mangan and zinc), amino acid total, fatty acid, and vitamins (A, C and E) levels. The study showed that bilih fish eggs meal contained protein 22,44-59,90%, fat 12,67-18,09%, moisture 7,33-10,62%, ash 3,25-5,43%, amino acid total 14,57-27, 50%, fatty acid 0,24-0,53%, mangan 1,38-1,66 mg/100 g, zinc 22,39-24,73 mg/ 100 g, vitamin  A 188,95-218,44 mg/100 g, vitamin C  10,42-18,08  mg/100 g and  vitamin  E 8,64-10,39 mg/100 g samples. It can be concluded that the egg meal of bilih fish is potentially be used as an enrichment ingredients of diet to improve fish growth and reproduction.  Keywords: Bilih fish eggs, proximate, amino acid, fatty acid, minerals, vitamin   ABSTRAK Tujuan dari penelitian adalah untuk mengetahui kandungan nutrisi tepung telur ikan bilih Mystacoleucus padangenesis Blkr sebagai informasi dasar dalam pengembangan pakan ikan menggunakan bahan lokal. Telur dikumpulkan dari nelayan.  Parameter yang diamati adalah proksimat (protein, lemak, air dan abu), mineral (mangan dan seng), total asam amino, asam lemak, dan vitamin (A, C, E). Hasil penelitian menunjukkan bahwa tepung telur ikan bilih mengandung protein 22,44-59,90%, lemak 12,67-18,09%, air 7,33-10,62%, abu 3,25-5,43%, asam amino total 14,57-27, 50%, asam lemak 0,24-0,53%, mangan 1,38-1,66 mg /100 g , seng 22,39-24,73 mg/100 g, vitamin A 188,95-218,44 mg/100 g, vitamin C 10,42-18,08 mg/100 g dan vitamin E 8,64-10,39 mg/100 g sampel. Sebagai kesimpulan adalah bahwa tepung telur ikan bilih memiliki potensi untuk digunakan sebagai bahan pengkayaan pakan untuk meningkatkan pertumbuhan dan reproduksi ikan. Kata kunci: telur ikan bilih, proksimat, asam amino, asam lemak, mineral, vitamin